Robust adaptive asymptotic tracking control of uncertain nonlinear systems subject to nonsmooth actuator nonlinearities - Zheng, Yunfeng; Wen, Changyun; Li, Zhengguo (International journal of adaptive control and signal processing, 2013)
SUMMARY In this paper, we control a class of uncertain nonlinear systems preceded by nonsmooth actuator nonlinearities such as dead zone, backlash, or hysteresis. Such nonlinearities will be handled in a unified framework by using a linear model with time‐varying parameters to approximate their input–output characteristics. Two robust adaptive control schemes based on Nussbaum gain technique are proposed. The controllers can guarantee global uniform boundedness of all signals and also asymptotic tracking. Simulation results also illustrate the effectiveness of the proposed schemes. Copyright © 2012 John Wiley & Sons, Ltd.